6-8(1+6x)=-2-4x

Simple and best practice solution for 6-8(1+6x)=-2-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-8(1+6x)=-2-4x equation:


Simplifying
6 + -8(1 + 6x) = -2 + -4x
6 + (1 * -8 + 6x * -8) = -2 + -4x
6 + (-8 + -48x) = -2 + -4x

Combine like terms: 6 + -8 = -2
-2 + -48x = -2 + -4x

Add '2' to each side of the equation.
-2 + 2 + -48x = -2 + 2 + -4x

Combine like terms: -2 + 2 = 0
0 + -48x = -2 + 2 + -4x
-48x = -2 + 2 + -4x

Combine like terms: -2 + 2 = 0
-48x = 0 + -4x
-48x = -4x

Solving
-48x = -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-48x + 4x = -4x + 4x

Combine like terms: -48x + 4x = -44x
-44x = -4x + 4x

Combine like terms: -4x + 4x = 0
-44x = 0

Divide each side by '-44'.
x = 0

Simplifying
x = 0

See similar equations:

| 1/2(-2)= | | -5(-17-13d)=-4(10-15d) | | 5(2n-4)-3=-36-3n | | -36-4a=-4(8a-5) | | 4x+3+4x=-15 | | 0=-8m^2-2m+2 | | -15s=-75 | | -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) | | x-(12)=-4 | | 2x+(2/(2x-12)) | | -7(4t+14)=-20-15t | | -7x=-28+11-4 | | y-19.25=x^2+6x+30.25 | | 3-x=2(1-4x)-6 | | 7t-12-2t=9+5t | | 2x+(2/2x-12) | | 2.5x+.5x=6+3.5 | | -(-20-4s)=-2(s+8) | | -8r=4(r-3) | | -50=19+y | | -5n-10=-(8n-1)-8n | | y=(x-2)-1 | | -(30)-(10)-43= | | 25200*(1/9) | | 80=1.8C+32 | | -255=-15k | | 10h=2(4h+13) | | 3a+9-6=21 | | 9.95m=m | | -3(x+5)=-3x-15 | | -18+2(j-12)=-12j | | 25200*(1/10) |

Equations solver categories